Development and validation of a drug clinical trial participation feelings questionnaire for cancer patients - Guo, Chaowei; Xing, Shujun; Zhao, Guo; Wu, Dawei; Li, Ning; Wang, Shuhang; Yu, Ling (Frontiers in Pharmacology, 2024)
Objective The study was designed to develop and validate a new Drug Clinical Trial Participation Feelings Questionnaire (DCTPFQ) for cancer patients. Methods Data collection and analysis involved a combination qualitative quantitative methods. There were two phases to this study. The phase Ⅰ involved developing a questionnaire to establish a list of items to be included in the pool: A theoretical framework was constructed based on transitions theory and the Roper-Logan-Tierney theory. Incorporating a theoretical framework, interviewing participants, and reviewing literature, 44 items were generated. After a Delphi consultation and a pilot test, 36 items proceeded to item analysis and exploratory factor analysis (EFA), and a four-factor structure with 21 items was formed. A confirmatory factor analysis (CFA), test-retest reliability, criteria-related validity, and internal consistency tests were conducted in phase II to examine psychometric properties. Results There were 21 items on the DCTPFQ, ranging from 1 (fully disagree) through 5 (fully agree). As a result of EFA and CFA, the four factors of DCTPFQ could be verified, including cognitive engagement, subjective experience, medical resources, and relatives and friends’ support. Test-retest reliability of the DCTPFQ was 0.840, and Cronbach’s alpha was 0.934. DCTPFQ is significantly correlated with the Fear of Progression Questionnaire-Short Form (r = 0.731, p<0.05) and the Mishel’s Uncertainty in Illness Scale (r = 0.714, p<0.05). Conclusion The DCTPFQ is a useful tool for measuring the drug clinical trial participation feelings among cancer patients.